A giant coronary artery ectasia successfully managed conservatively - Waqas Ullah; Mishal Shaukat; Asrar Ahmad; Zain Ali; Maryam Mukhtar; Mamoon Ur Rashid (Journal of Community Hospital Internal Medicine Perspectives, 2020)
Coronary artery aneurysms (CAA) is a rare condition characterized by abnormal dilatation of the coronary arteries. We present a case of a 77-year-old gentleman who presented with atypical chest pain and was found to have elevated cardiac enzymes. He underwent diagnostic left heart catheterization which revealed left main CAA and significant left circumflex stenosis. The patient was administered medical therapy and was discharged home in a stable condition. The purpose of this report is to highlight a rare case of a large CAA which was successfully managed conservatively.